When is an illusion not an illusion? An alternative view of the illusion concept - Rogers, Brian (Frontiers in Human Neuroscience, 2022)
What is an “illusion”? I would like to argue that (A) there is no coherent and meaningful definition of the word “illusion” and (B) the majority of the things we have previously labelled as “illusions” can be better categorised into three classes of perceptual effects: (i) those that should not be regarded as illusory according to any definition; (ii) those that are simply consequences of “how our perceptual systems work” and (iii) those that are a consequence of using artificial or impoverished stimulus situations.